Disentangling effects of droughts and heatwaves on alpine periphyton communities: A mesocosm experiment - Tamika Nagao; Rolf Vinebrooke (Limnology and Oceanography Letters)
Abstract The accelerating rate of global climate change at higher elevations and latitudes is increasing the potential for extreme climatic events. Here, a knowledge gap exists in how the order of exposure to, and duration of droughts and heatwaves affect their cumulative impact on aquatic communities. We tested experimentally for the legacy effects of simultaneous vs. sequential exposures to drought and heatwave on sediment‐dwelling algal communities (epipelon) from small fishless alpine lakes. In both simultaneous, and sequential exposure treatments involving drought followed by a heatwave, the negative effect of drought masked the effects of warming on chlorophyll‐inferred algal biomass and taxonomic composition. Reversal of order of exposure (i.e., heatwave followed by drought) lowered their cumulative effect on community structure. These findings highlight the potential for drought events to dominate over heatwaves in altering shallow littoral ecosystems at high elevations under a rapidly warming climate.